THU0308 Secondary Antiphospholipid Syndrome Nephropathy and Lupus Nephritis: A Case-Control Study. (23rd January 2014) - Pérez Velásquez, C. E.; Isenberg, D.; Croca, S.
Abstract : Background: The presence of antyphospholipid syndrome nephropathy (APSN) in systemic lupus erythematosus (SLE) patients has been associated with more severe clinical presentations, and there was evidence that SLE patients with antiphospholipid (APL) antibodies were more likely to develop chronic renal failure. Objectives: To compare the demographic data, clinical manifestations, laboratory findings and outcome of renal involvement in lupus patients with secondary APSN vs patients with lupus nephritis (LN) alone. Methods: We reviewed the cohort of SLE patients (n=600 patients) in our centre. We identified 6 patients whose renal biopsy findings fulfilled typical features of LN plus vascular APSN; each case was matched with 2-3 patients with LN only for sex, ethnicity and age at biopsy (± 4.5 years). Data were analyzed by Student t test for comparison of quantitative variables and the paired t test for comparison of each matched set. The associations between categorical variables were tested using chi-squared test and Fisher´s exact test. Results: The frequency of SLE patients with positive APL antibodies without evidence of clinical APS was 32%. renal disease (RD) was found in 31.8% of the total cohort of our SLE patients. The incidence of secondary APS in the whole cohort of SLE patients was 4.3%, of whom 56% had RD, but only 43% had typical features of APS on biopsy. The age at diagnosis in the secondary APSN cases ranged from 13 to 59 years (median = 25, SD = 15.8). The duration of the disease from the time of diagnosis to January 2012 in the secondary APS cases ranged from 9 to 32 years (median = 16.5 years, SD = 9.2). The secondary APSN cases and the LN controls did not differ with regard to age at diagnosis or disease duration. The time between the SLE diagnosis and the RD diagnosis was lower in the controls (median = 1 year, SD = 2.3) than in secondary APSN cases (median = 3 years, SD = 4.5). The percentage of patients who developed RD within 5 years of SLE diagnosis was higher in the LN controls (82.3%) vs secondary APSN cases (66.7%). Immunologically, we found significant differences between secondary APSN cases and the LN controls for antibodies IgG anti-cardiolipin (p < 0.01) and lupus anticoagulant antibodies (p < 0.05). However, there were no statistically significant differences in the clinical manifestations between the groups. World Health Organization grade IV lupus glomerulonephritis was the most comon lession seen in both groups (50% cases vs 58.8% controls). Although, of the 17LN controls patients, 3 of them (17.6%) developed end-stage renal disease (ESRD) and subsequently underwent renal transplantation, no patient in the secondary APSN cases had developed ESRD until January 2012. Three Secondary APSN cases have died (50% vs 11.8% of matches). Conclusions: We found a relatively low frequency of APS in our cohort of SLE patients compared with other studies. The renal diseases associated with secondary APS include a variety of nephropathies, and the antibodies IgG anti-cardiolipin and lupus anticoagulant were more prevalent in this patients. As in the literature, the duration of RD was shortest in secondary APSN cases and the mortality was higher in this group too. Disclosure of Interest: None Declared